Analysis Of Lithium Ion Battery Characteristics In Electric Motors - Syahrobi, Syahrobi; Muhammad Erpandi Dalimunthe; Zuraidah Tharo (Sean Institute, 2025)
Lithium-ion (Li-ion) batteries are one of the battery technologies widely used in electric motorcycles (EVs) because they have high efficiency and good durability. This battery functions as the main energy source for electric vehicles and is an important component in supporting vehicle performance. This study aims to analyze the characteristics of Lithium-ion batteries in electric motorcycles by considering factors such as operating temperature, voltage, and the influence of speed and terrain. Tests were carried out on flat and uphill tracks with speed variations of 10 km/h, 30 km/h, and 50 km/h. The results showed that Lithium-ion batteries tend to experience a faster increase in temperature when used at high speeds, but the battery voltage remains stable during the Discharge and Charging process without any significant spikes. These findings provide insight into the performance of Lithium-ion batteries in electric vehicles, as well as the importance of temperature management to maintain optimal battery performance.